A REVIEW ON RECENT ADVANCES IN ANIMAL BIOTECHNOLOGY - Sarada Bhandari; Lokendra Nath Yogi (Science Heritage Journal)
Animal biotechnology represents a cutting-edge field that has revolutionized our interactions with the animal kingdom. Recent advancements encompass various domains, including genetic editing techniques like CRISPR-Cas9, which allow precise genetic modifications for improved animal health and product quality. Cloning and reproductive technologies offer opportunities to preserve rare genetic traits and enhance livestock production, albeit accompanied by ethical and genetic diversity challenges. Transgenic animals, engineered with foreign genes, serve purposes from increased productivity to disease modeling, raising ethical and regulatory concerns. Disease resistance strategies involve selective breeding and gene editing to bolster animals’ immunity, promoting sustainable farming practices. Biopharming utilizes genetically modified animals for large-scale pharmaceutical production, balancing potential benefits with containment and safety issues. Conservation efforts employ advanced genetic and reproductive techniques to protect endangered species, necessitating careful ethical and ecological considerations. Animal biotechnology promises transformative possibilities but underscores the importance of responsible progress and ethical frameworks.